Enhanced mechanical properties in ceramic multilayer composites through integrating crystallographic texture and second-phase toughening. Issue 22 (15th November 2021) - Sun, Yuan; Xie, Hang; Liu, Linjing; Kou, Qiangwei; Zhang, Shantao; Yang, Bin; Cao, Wenwu; Chang, Yunfei
Abstract: Inherent brittleness and low mechanical reliability usually inhibit the application of ceramic materials in many structural applications. In this work, we demonstrate that integrating crystallographic texture and second-phase toughening strategies can effectively improve fracture resistance and mechanical reliability in alumina multilayer composites. Composites consisted of equiaxed (1- x )Al2 O3 - x ZrO2 and highly [0001]-textured Al2 O3 layers were fabricated, and effects of ZrO2 amount on fracture behavior and mechanical properties of the composites were studied. Increasing ZrO2 amount x results in larger thermal expansion difference between equiaxed and textured layers. The composites with equiaxed layers containing 30 vol% ZrO2 exhibit high apparent fracture toughness K apt, c ~11.7 MPa·m 1/2 and work of fracture γWOF ~1540 J/m 2, which correspond respectively to about 260% and 410% enhancements relative to those without ZrO2 addition. Moreover, adding ZrO2 remarkably reduces sensitivity of failure stress to flaw size in the multilayer composites, and the failure stress substantially increases with increasing ZrO2 content. The greatly enhanced mechanical performance achieved here can be mainly attributed to higher magnitude of compressive stresses, more crack bifurcations and longer crack deflection paths within the textured layers. This work can provide important guidelines for developing novel "bio-inspired" materials with improved fracture resistance and flaw tolerance behavior.